Faktor yang Berhubungan dengan Rendahnya Kunjungan Ibu Balita ke Posyandu Camar Desa Sialingan Kabupaten Muara Enim Tahun 2021 - Vina Aprillia Damayanti; Eka Afrika; Merisa Riski (Universitas Batanghari Jambi, 2022)
Globally, there are 2.5 million newborn deaths and 1.5 million infant deaths. Efforts to accelerate the decline in IMR and AKI are providing services with posyandu. The purpose of this study was to determine the relationship between knowledge, attitudes, work and distance with the low visits of mothers under five to the Posyandu. The research method used an Analytical Survey with a Cross Sectional approach with a population of all mothers with toddlers aged 2-59 months at the Camar Posyandu totaling 194 people. Sampling using purposive sampling a number of 66 respondents. Data collection using a questionnaire sheet. Data analysis used univariate and bivariate analysis with chi square test. The results showed that there was a relationship between knowledge (p value = 0.003), attitude (p value = 0.036), occupation (p value = 0.012) and distance (p value = 0.039) with the low visitation of mothers of children under five to the Camar Posyandu, Sialingan Village, Belida Darat District in 2021. The conclusion is that there is a relationship between knowledge, attitude, work and distance with low visits by mothers of children under five to the Camar Posyandu, Sialingan Village, Belida Darat District in 2021. It is hoped that health officers can provide information about posyandu time and the benefits of posyandu to mothers who have children under five, so that understanding mothers about posyandu will be even better and can increase the activity of mothers who have toddlers to do posyandu.